2016
DOI: 10.3390/catal6020028
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Dialkyl Hexane-1,6-Dicarbamate from 1,6-Hexanediamine, Urea, and Alcohol over Zinc-Incorporated Berlinite (ZnAlPO4) Catalyst

Abstract: Dialkyl hexane-1,6-dicarbamate was synthesized, for the first time, by a one-pot reaction of 1,6-hexanediamine (HDA), urea, and alcohols, including methanol, ethanol, propanol, and butanol, in a self-designed batch reactor, using zinc-incorporated berlinite (ZnAlPO 4 ) as a catalyst. The yield of dibutyl hexane-1,6-dicarbamate (2) was systematically investigated as a function of Zn/Al molar ratio, reaction temperature, reaction time, catalyst usage and urea/HDA/butanol molar ratio. Based on these studies, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Thus, it turns out to be quite difficult to establish a reaction mechanism and a kinetic model. The reactivity of isocyanate vs. different functional groups follows the order: Primary amine > secondary amine > hydroxyl > acid > anhydride > epoxide [ 24 ]. The reaction between an alcohol and an isocyanate group to form a carbamate ester is moderate, hence is usually catalyzed by bases, mainly tertiary amines like TEA [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it turns out to be quite difficult to establish a reaction mechanism and a kinetic model. The reactivity of isocyanate vs. different functional groups follows the order: Primary amine > secondary amine > hydroxyl > acid > anhydride > epoxide [ 24 ]. The reaction between an alcohol and an isocyanate group to form a carbamate ester is moderate, hence is usually catalyzed by bases, mainly tertiary amines like TEA [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reaction is exothermic and is also catalyzed by tertiary amines. It has been demonstrated that the isocyanate reactivity with water and primary hydroxyl group is comparable, and more than double that with carboxylic acids [ 24 ]. Isocyanates also react with amines to give ureas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, isocyanate was prompted to have reaction with the functional groups of GO as side reaction, whether from the edge carboxylic acid, surface hydroxyl, or epoxide in producing amides or carbamate esters [57]. As stated by Sun et al [58], the sequence of isocyanate reactivity with different functional group was in the sequence as primary amine > secondary amine > hydroxyl > acid > anhydride > epoxide. Due to the reactivity of isocyanate versus different functional group, isocyanate had higher reactivity with the hydroxyl group compared to the other functional group of GO.…”
Section: Fourier-transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…Conventionally, the production of urethanes involves the employment of phosgene, which is extremely toxic and harmful to the environment and human beings. Therefore, there have been tons of endeavors for producing carbamates via phosgene-free pathways [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Among them, the catalytic reductive carbonylation of nitroarenes is regarded as one of the promising routes [6][7][8][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%